Rewriting Female Ageing: Positive Later-Life Narratives in Post-COVID Cinema from the Global North - Rodriguez (Magyar Gerontológia, 2025)
Ageing has surged as a central theme during the COVID-19 pandemic, gaining visibility in social and cultural discourse and narratives. This new cultural attention opened space for an in depth analysis of how later life is framed within narrative cinema, particularly for women.